Development and evaluation of STAR – an expert digital platform supporting training and delivery of cessation interventions by healthcare professionals in Poland. - Herbeć, Aleksandra; Janik-Koncewicz, Kinga; McEwen, Andy; West, Robert; Zatoński, Witold (Journal of Health Inequalities, 2017)
Access to smoking cessation treatment, and in particular to dedicated stop smoking services, is limited in many countries. Digital tools could support healthcare professionals (HCPs) with limited training and resources to deliver evidence-based cessation treatment to their patients. The presented project aims to develop, evaluate and disseminate the STAR (Smoking Treatment Advisory Resource) Programme – a novel internet-based platform acting as a support tool and expert system for data gathering, delivery of evidence-based treatment, networking, and training for HCPs offering cessation treatment. This will be accomplished through three phases. Phase 1 will be devoted to development of STAR, including formative research, expert consultations and interviews with HCPs and patients who smoke. Phase 2 will involve mixed-methods evaluation of STAR. Finally, during Phase 3 the STAR Programme will be refined and promoted among a wider community of HCPs and patients, and the results disseminated. STAR will be evaluated using mixed-methods, including quantitative assessments of changes in key indicators from baseline to immediate post-training and follow-up; as well as qualitative evaluation. It is expected that the project will result in the development of an acceptable and sustainable Programme that will increase the number of HCPs delivering evidence-based cessation support.